PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT KALBE FARMA TBK PERIODE 2013-2023 - Inas Nur Syahla; Sutiman (Journal of Research and Publication Innovation, 2025)
This study aims to determine the influence of Current Ratio (CR) and Debt to Equity Ratio (DER) simultaneously on Return On Assets (ROA) at PT Kalbe Farma Tbk for the 2013-2023 period, both partially and simultaneously. The research used is descriptive research with a quantitative approach. The data source used is the financial report data of PT. Kalbe Farma Tbk for the years 2013-2023. The results of the first hypothesis test obtained a calculated t value> t table or -3.600> 2.26216 strengthened by the Sig value. 0.006 <0.05 then H0 is rejected and H1 is accepted, so it can be concluded that partially the Current Ratio variable has a significant negative effect on (ROA). The results of the second hypothesis test obtained a calculated t value> t table or 3.387> 2.26216 strengthened by the Sig value. 0.008 < 0.05 then H0 is rejected and H2 is accepted, so it can be concluded that partially the Debt to Equity Ratio variable has a significant positive effect on expected (ROA). The results of the third hypothesis test obtained a value of F count> F table or 5.771> 4.46 strengthened by the Sig value. 0.028 < 0.05 then H0 is rejected and H3 is accepted, so it can be concluded that simultaneously the Current Ratio and Debt to Equity Ratio variables have a significant positive effect on expected (ROA).